MEDIA SOSIAL SEBAGAI SARANA KOMUNIKASI MASYARAKAT PERANTAUAN (STUDI DESKRIPTIF PENGGUNAAN WHATSSAPP GRUP PADA SUKU GUCI DT MARAJO KILANGAN) - Reni Novia (Institut Bisnis Muhammadiyah Bekasi, 2022)
The research that is backgrounded on the use of social media as a communication tool for overseas people from West Sumatra, the Gucy Dt Marajo Kilangan Tribe has a problem formulation of How Social Media as a means of communication for overseas communities (Descriptive Study of the Use of WhatsApp Groups in the Dt Marajo Kilangan Urn Tribe). The purpose of this study was to find out how social media as a means of communication for overseas communities (descriptive study of the use of Whatsapp Groups in the Datuk Marajo Kilangan Urn Tribe) A descriptive research method with this qualitative approach, data collection was carried out by conducting interviews with 4 key informants and making direct observations on the object of study. Data analysis or processing is an effort to search and compile observation records, in-depth interviews, and documentary studies systematically. The object of study is the gucy tribe Dt Marajo who are members of the Whatsapp Group. The validity of the data is carried out by triangulation of source data, as well as observation. This research uses the theory of Coordinate Management of Meaning, as well as the concept of using social media.